ALIH KODE DAN CAMPUR KODE DALAM NOVEL 99 CAHAYA DI LANGIT EROPA KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA: SUATU KAJIAN SOSIOLINGUISTIK - Lianiska, Wiwik; Faizah AR, Hasnah; Charlina, Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study is about Shifted And Mixed Code in Novel the 99 Light on the Sky of Europe by Hanum Salsabiela Rais and Rangga Almahendra: An Assessment of Sociolinguistics. This research will discuss a few things, namely the language of the source code switching and code-mixing and then factors that cause code switching and code-mixing. This study aims to determine and describe the language of the source and the factors that cause the code switching and code-mixing happen. After the research was conducted, the obtained result of this study is 223 of data shif code and code-mixing. From this 223 data divided into 39 shif data rather code and data is code-mixing. From 39 of the data shif code data and 184 mix code consisting of 19 internal data, 13 data is external, 7 data switching between foreign languages , while language is the source of the shif come from 5 languages (Indonesian, English, German, Arabic, and Spanish). Meanwhile, of the 184 code-mixing data is divided into 21 data that sourced from Indonesian, 116 data that sourced from English, 23 data that sourced from German and Arabic, and the last one of the data is sourced from the Spanish.Keywords: Instead of code, code-mixing, sociolinguistics, novel